The influence of professional identity on learning engagement among teacher education students: a latent profile analysis - Chen, Yuanrui; Qi, Xiaodong; Zhang, Jingwen; Ma, Mingyang; Yang, Xiaobo; Baek, Jongnam (Frontiers in Education, 2025)
IntroductionThis study investigates the influence of latent categories of professional identity on learning engagement among teacher education students.MethodsLatent Profile Analysis (LPA) was employed with a sample of 1,059 teacher education students.ResultsThree distinct groups were identified: high, medium, and low professional identity groups. Gender and voluntary choice of teacher education major showed clear variations across groups. Females were more prevalent in the medium professional identity group, whereas involuntary students were disproportionately represented in the low and medium professional identity groups. The impact of professional identity on learning engagement showed a descending trend from high to the medium to low groups. Notably, in the medium and high professional identity groups, professional values and efficacy exerted a strong influence on learning engagement. By contrast, in the low professional identity group, overall professional identity demonstrated a significant impact on learning engagement.DiscussionThis study reveals the heterogeneity of teacher education students’ professional identity and its underlying mechanisms influencing learning engagement, offering insights for the design of differentiated teacher education and professional development programs.